1984
DOI: 10.1159/000469481
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandins Modulate Arterial Cholesteryl Ester Metabolism

Abstract: Cholesterol and cholesteryl esters (CE) are the two major classes of lipids which accumulate in arteries during human arteriosclerosis. Mechanisms responsible for this arterial lipid accretion remain to be fully elucidated. In recent years, we have suggested that prostaglandins may have an important role in the modulation of intracellular arterial CE metabolism through their interaction with cyclic nucleotides. This hypothesis was based on observations that arteriosclerotic arteries produce less prostaglandins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1986
1986
1990
1990

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…It has been reported that prostaglandins modulate arterial cholesteryl-ester metabolism by stimulating the enzyme cholesteryl-hydrolase (44). Therefore, an increased prostacyclin production in the HDL-treated group might also account for the observed antiatherogenic effect.…”
Section: Discussionmentioning
confidence: 95%
“…It has been reported that prostaglandins modulate arterial cholesteryl-ester metabolism by stimulating the enzyme cholesteryl-hydrolase (44). Therefore, an increased prostacyclin production in the HDL-treated group might also account for the observed antiatherogenic effect.…”
Section: Discussionmentioning
confidence: 95%
“…It is possible that the fats affect the prostaglandin metabolism in the arterial wall. 26 It has been observed that feeding olive oils to rabbits results in a higher arterial PGI 2 production than feeding corn oil. 27 The effect of these oils may be caused by their fatty acid content but may also be due to one or more of the many other constituents in the oils.…”
Section: Downloaded Frommentioning
confidence: 99%
“…17) [105]. On the basis of the investigations discussed here, this local deficiency [104,105] in prostacyclin could result in the vascular tissue no longer being capable of effectively counteracting further deposition of cholesterol esters, so that the atheromatosis would advance rapidly. The cAMP in its turn stimulates the breakdown of the cholesterol esters by activating cholesterol ester hydrolase.…”
Section: Antiatherogenic Actionmentioning
confidence: 91%